EMPLOYEES’ MENTAL HEALTH AS AN INVESTMENT FOR THE ENTERPRISE: FROM ORGANIZATIONAL ASPECTS TO THE ACCOUNTING DIMENSION - Bashchuk, Iryna (Current Problems of Sustainable Development, 2026)
The study examines employees’ mental health as a strategic resource of an enterprise and an important object of management and accounting-analytical support. The paper systematizes theoretical approaches to defining the essence of mental health within the framework of HR management and substantiates its significant impact on labor productivity, employee motivation, organizational resilience, and overall business performance. Particular attention is paid to the role of a psychologically safe work environment in enhancing employee engagement, strengthening organizational commitment, and reducing the risks of professional burnout, stress-related disorders, and staff turnover. The research justifies the feasibility of interpreting expenditures on mental health support programs as long-term investments in human capital, which contribute to sustainable enterprise development, value creation, and increased competitiveness in a dynamic business environment. In this context, the necessity of developing appropriate accounting and analytical tools for the identification, measurement, valuation, and disclosure of such investments is emphasized, taking into account both financial and non-financial indicators. Furthermore, the study outlines key directions for integrating HR analytics, digital technologies, and data-driven approaches into enterprise management systems to monitor employees’ psycho-emotional state, predict potential risks, and assess the effectiveness of mental health initiatives. It is argued that a comprehensive approach to managing employees’ mental health requires the formation of a robust information and analytical base that supports managerial decision-making, enhances transparency in reporting, and aligns organizational practices with the principles of sustainable development and corporate social responsibility.